KONTRIBUSI PEMIKIRAN MUHAMMAD SAW PRA DAN PASCA KENABIAN ERA MAKKIAH - Agus Jaya (Ta'dib: Jurnal Pendidikan Islam, 2011)
Muhammad is the greatest phenomenon in human history. Signs He enshrined in the presence of the holy scriptures is  as a justification former glory. His presence was expected by every group and interest, although later become a boomerang for them because the treatise was carrying remodel beliefs and traditions handed down from their ancestors. The suffering experiences completed His life’s history  as a candidate of  a prophet. Born with orphan status, grew by profession and lived as a shepherd, had suffering experiences has  formed  the identity of Muhammad to become an intelligent and wise leader. Muhammad's intelligence and wisdom in deciding the issue and genius as well as the accuracy of missionary strategy embedded in the period of Mecca is the contribution of thinking which is priceless.